Residuos sólidos provenientes de la actividad bananera y sus efectos en la calidad ambiental del cantón Valencia. Año 2012. Plan de reciclaje. - Lara Sánchez, Hugo Alcibiades (2013)
Banana crops have settled predominantly in high vocation agricultural mechanized or traditional land and with great hydrological richness, these areas are of medium and high vulnerability to the productive processes, and are not recommended for intensive, industrial, mining, urban development and recreation. However, due to the importance that has been the establishment of agro-industry in these areas, protection and management plans environmental conservation purposes but without neglecting the productivity are required. The intensive use of inputs in agricultural work produces higher organic loads, whose custodians are the bodies of water, resulting in processes of eutrophication and the progressive modification of the water quality by the dumping of sewage and the widespread use of these products. The present research work describes generating major causes of waste in the activities of the banana industry in Valencia. Identifies the materials that compose this waste and explains their effects on environmental elements soil, water and air. This purpose will be used methods of observation and analysis to determine and quantify the types and quantities of solid waste from banana activity in the area of Valencia. Also suggests a management plan in order to mitigate the impact on the population of the area of Valencia.